High cortisol and the risk of Alzheimer disease: A protocol for systematic review and meta-analysis. Issue 39 (1st October 2021) - Yao, Zhuang; Liu, Bin; Wang, Yueyang; Dong, Xiaohong
Abstract: Background: Morning cortisol levels have been reported to be elevated among patients with Alzheimer disease (AD). We perform a protocol for systematic review and meta-analysis to assess morning central or peripheral cortisol levels in AD patients as compared with cognitively normal individuals. Methods: Studies were identified through systematic searches in August 2021 with no restrictions on date and time, language, and publication status using the following bibliographic databases: Embase, Medline, PubMed, Web of Science, Science Direct, and the Cochrane Library. Studies were identified using search terms related to cortisol, Alzheimer disease, and cognitive impairment. The study quality of included papers was evaluated using the "National Institutes of Health (NIH) quality assessment tool for observational cohort and cross-sectional studies." Statistical analyses were performed using Stata (version 14, StataCorp, College Station, TX). Results: The findings of this study will be submitted to peer-reviewed journals for publication. Conclusion: Morning cortisol was elevated in AD patients and may have diagnostic and prognostic values for AD.